Pengaruh Corporate Social Responsibility (CSR) dan Beban Pajak terhadap Kinerja Keuangan Bank Jambi Periode 2020-2024 - Olivia, Dina; Pradana, Aditya; Efrina S., Liona (ARZUSIN, 2026)
Corporate Social Responsibility (CSR) and tax expense are financial and non-financial factors that can influence a company’s financial performance. This study aims to analyze the effect of CSR and tax expense on the financial performance of Bank Jambi for the 2020–2024 period, measured using Return on Assets (ROA). This study used a quantitative approach with multiple linear regression analysis based on secondary data obtained from Bank Jambi’s annual financial reports. The results showed that CSR had a positive but insignificant effect on ROA, whereas tax expense had a positive and significant effect on financial performance. This finding indicates that an increase in tax expense is in line with an increase in company profit, while the contribution of CSR to financial performance has not been partially proven to be significant. Simultaneously, CSR and tax expense had a significant effect on financial performance, with a coefficient of determination of 51.6%. The conclusion of this study affirms that Bank Jambi’s financial performance is influenced by a combination of financial and non-financial factors, although CSR has not had a significant partial effect. These findings imply the importance of efficient tax expense management and the strengthening of CSR strategies so that they can make a more optimal contribution to the company’s financial performance.